Fast myocardial T1 mapping using cardiac motion correction. Issue 2 (16th August 2019) - Becker, Kirsten M.; Blaszczyk, Edyta; Funk, Stephanie; Nuesslein, André; Schulz‐Menger, Jeanette; Schaeffter, Tobias; Kolbitsch, Christoph
Abstract : Purpose: To improve the efficiency of native and postcontrast high‐resolution cardiac T1 mapping by utilizing cardiac motion correction. Methods: Common cardiac T1 mapping techniques only acquire data in a small part of the cardiac cycle, leading to inefficient data sampling. Here, we present an approach in which 80% of each cardiac cycle is used for T1 mapping by integration of cardiac motion correction. Golden angle radial data was acquired continuously for 8 s with in‐plane resolution of 1.3 × 1.3 mm 2 . Cine images were reconstructed for nonrigid cardiac motion estimation. Images at different TIs were reconstructed from the same data, and motion correction was performed prior to T1 mapping. Native T1 mapping was evaluated in healthy subjects. Furthermore, the technique was applied for postcontrast T1 mapping in 5 patients with suspected fibrosis. Results: Cine images with high contrast were obtained, leading to robust cardiac motion estimation. Motion‐corrected T1 maps showed myocardial T1 times similar to cardiac‐triggered T1 maps obtained from the same data (1288 ± 49 ms and 1259 ± 55 ms, respectively) but with a 34% improved precision (spatial variation: 57.0 ± 12.5 ms and 94.8 ± 15.4 ms, respectively, P < 0.0001) due to the increased amount of data. In postcontrast T1 maps, focal fibrosis could be confirmed with late contrast‐enhancement images. Conclusion: The proposed approach provides high‐resolution T1 maps within 8 s. Data acquisition efficiency for T1 mapping was improved by a factor of 5 by integration of cardiac motion correction, resulting in precise T1 maps.